Effect of orthopedic and functional orthodontic treatment in children with obstructive sleep apnea: A systematic review and meta-analysis. (February 2023) - Bucci, Rosaria; Rongo, Roberto; Zunino, Benedetta; Michelotti, Ambrosina; Bucci, Paolo; Alessandri-Bonetti, Giulio; Incerti-Parenti, Serena; D'Antò, Vincenzo
Abstract: Orthodontic treatment is suggested in growing individuals to correct transverse maxillary deficiency and mandibular retrusion. Since, as a secondary effect, these orthodontic procedures may improve pediatric obstructive sleep apnea (OSA), this systematic review assessed their effects on apnea-hypopnea index (AHI) and oxygen saturation (SaO2). Twenty-five (25) manuscripts were included for qualitative synthesis, 19 were selected for quantitative synthesis. Five interventions were analyzed: rapid maxillary expansion (RME, 15 studies), mandibular advancement (MAA, five studies), myofunctional therapy (MT, four studies), and RME combined with MAA (one study). RME produced a significant AHI reduction and minimum SaO2 increase immediately after active treatment, at six and 12 months from baseline. A significant AHI reduction was also observed six and 12 months after the beginning of MAA treatment. MT showed positive effects, with different protocols. In this systematic review and meta-analysis of data from mainly uncontrolled studies, interceptive orthodontic treatments showed overall favorable effects on respiratory outcomes in pediatric OSA. However, due to the low to very low level of the body evidence, this treatment cannot be suggested as elective for OSA treatment. An orthodontic indication is needed to support this therapy and a careful monitoring is required to ensure positive improvement in OSA parameters.